Risk Factors for Stunting in Toddlers of Fishermen Families in the Coastal Area of Mojo Pemalang - Lestari, Ayu Dwi Indah; Budiono , Irwan (Jurnal Kesehatan, 2025)
Pendahuluan: Stunting adalah kondisi gagal tumbuh yang diakibatkan oleh akumulasi ketidakcukupan asupan nutrisi saat kehamilan hingga bayi mencapai usia 24 bulan. Kejadian stunting  di Indonesia masih menjadi masalah gizi yang dominan terutama di wilayah pesisir. Metode: Penelitian ini dilaksanakan pada bulan Mei hingga Juni 2023. Jenis penelitian adalah kuantitatif observasional analitik dengan desain case control. Jumlah sampel dalam penelitian sebanyak 60 balita keluarga nelayan usia 24 – 59 bulan. Teknik pengambilan data dengan purposive sampling. Instrumen penelitian adalah microtoise, wawancara dengan kuesioner, lembar SQ-FFQ (Semi Quantitative Food Frequency Questionnare),  dan lembar observasi. Analisis dilakukan dengan analisis univariat, bivariat dan multivariat. Hasil: Hasil penelitian didapatkan bahwa  BBLR (p= 0,492), riwayat ASI Eksklusif (p=0,000; OR= 17,875), riwayat penyakit ISPA (p=1,000), riwayat penyakit diare (p=0,424; OR= 2,800), tingkat kecukupan energi (p=0,000; OR= 32,500), tingkat kecukupan protein (p=0,000; OR= 28,000), pekerjaan ayah (p=0,000, OR= 9,036), pendapatan keluarga (p=0,002; OR= 6,909), kelompok kerja nelayan (p=0,03; OR= 6,538), dan akses air bersih (p=0,001; OR= 8,000). Simpulan: Faktor risiko yang berhubungan dengan kejadian stunting antara lain riwayat ASI Eksklusif, tingkat kecukupan energi, tingkat kecukupan protein, pekerjaan ayah, pendapatan keluarga, kelompok kerja nelayan, dan akses air bersih. Berdasarkan hasil analisis uji multivariat dihasilkan bahwa faktor risiko yang paling dominan adalah tingkat kecukupan protein dengan nilai OR 68,167.   Introduction: Stunting is a condition of growth failure caused by the accumulation of inadequate nutritional intake during pregnancy until the baby reaches 24 months of age. The incidence of stunting in Indonesia is still a dominant nutritional problem, especially in coastal areas. This study aims to determine the factors that influence the incidence of stunting in toddlers of fishermen families. Methods: This study was conducted from May to June 2023. The type of research is quantitative observational analytic with case control design. The number of samples in the study were 60 toddlers of fishing families aged 24 - 59 months. The technique of determining the sample with purposive sampling. The research instruments were microtoise, interview with questionnaire, SQ-FFQ (Semi Quantitative Food Frequency Questionnaire) sheet, and observation sheet. Analysis was done by univariate analysis, chi-square test and multiple logistic regression test. Results: There is a relationship between exclusive breastfeeding history, energy adequacy level, protein adequacy level, father's occupation, family income, fishermen's work group, and access to clean water with the incidence of stunting in toddlers of fishermen families. The results showed that the level of protein adequacy had the strongest influence with an OR value of 68.167. Conclusion: This study suggests that people in coastal areas are advised to consume food intake with balanced nutrition, consume foods with protein sources such as fish, create a clean and healthy environment, and improve the health status of toddlers.